Results of treatment of herniated nucleus pulposus with microdiscectomy - C. Chavasiri (2020)
© Journal of the Medical Association of Thailand 2019 Background: Microdiscectomy is becoming a popular minimally invasive spine surgery for lumbar disc herniation. This procedure is performed by both neurosurgeons and orthopedists. Objective: The present study aimed to evaluate the efficacy and outcomes of microdiscectomy for treatment of Thai patients with lumbar disc herniation. Materials and Methods: This retrospective chart review included 112 Thai patients who underwent microdiscectomy for lumbar disc herniation during November 2006 to June 2014 at Siriraj Hospital (Bangkok, Thailand). Data collected from medical records and a telephone conversation included demographic, anthropometric, clinical, intra-operative, and postoperative data. Oswestry Disability Index (ODI) and EuroQol instrument (EQ5D5L) were used for outcome evaluation. Results: The average age of patients was 45.7+13 years (range: 18 to 72), and there were 62 males and 50 females. Average body mass index (BMI) was 24.4+4.2 kg/m2 (range: 15.8 to 44.3). The most commonly treated level was L4 to 5. Mean operative time was 92.7+33.1 minutes per level (range: 50 to 220), and the average length of stay was 3.8+2.1 days (range: 2 to 13). Mean estimated blood loss was 60.1+66.5 ml (range: 5 to 400). Average follow-up was 51.3+38.8 months (range: 0.5 to 118). Seventy-three percent (73.2%) of patients were followed-up for at least 1 year, 63.4% were followed-up for at least 3 years, and 50% were followed-up for at least 4 years. Sixty-three patients (63.4%) completed the postoperative outcome questionnaires. Mean ODI score was 62.9+16.6 (range: 20 to 93.3) pre-operatively, and 11.3+12.2 (range: 0 to 60) postoperatively (p<0.001). Mean EQ-5D-5L was 0.016+0.247 (range: -0.254 to 0.861) pre-operatively, and 0.938+0.162 (range: 0.197 to 1) postoperatively (p<0.001). Conclusion: Microdiscectomy was found to be an effective surgical treatment for Thai lumbar disc herniation patients, with minimal blood loss, short hospital stay, and low complication rate.